Ultra-thin-ply CFRP Bouligand bio-inspired structures with enhanced load-bearing capacity, delayed catastrophic failure and high energy dissipation capability - Mencattelli,L; Pinho,ST (Composites Part A: Applied Science and Manufacturing, 2020)
In this work, we demonstrate for the first time that the inherent low performance to out-of-plane loading of thin-ply Carbon Fibre Reinforced Plastics (CFRPs) can be overcome with tailored bio-inspired Bouligand microstructures. To this end, we designed, manufactured ultra-thin-ply CFRP Bouligand laminates and conducted an original study which combines full-penetration quasi-static indentation tests, in-situ three-point bending tests conducted under a SEM and detailed analytical modelling. We investigated a wide range of mismatch (pitch) angles [2.5°, 5°, 10°, 20°, 45°], showing that decreasing pitch angles simultaneously achieved a larger (i) load-bearing capability, (ii) delay in catastrophic failure and (iii) total dissipated energy. We then investigated the role of the pitch angle on the activation of the highly dissipative sub-critical failure mechanisms responsible for the high mechanical performances achieved by small pitch angles laminates. Our investigation clearly shows that, with ultra-thin-ply CFRP, smaller pitch angles achieve higher damage tolerance and structural integrity.